PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN OLEH KAPAL PERANG REPUBLIK INDONESIA (KRI) DALAM PERSPEKTIF UNDANG-UNDANG RI NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Darmika, Ketut (Jurnal Hukum dan Peradilan, 2015)
Illegal fishing is a serious problem that must be addressed because it is very harmful to the preservation of resources and economically detrimental for the country. According to Article 73 paragraph (1) of Law Number 45 Year 2009 investigation of criminal offenses in the field of fisheries carried out by the Civil Servant of Fisheries Investigators, Navy Investigators (TNI AL), and/or Police Investigator of the Republic of Indonesia. Furthermore, in Article 69 paragraph (4) the investigator and/or fisheries supervisor can perform specific actions such as burning and/or sinking of foreign-flagged fishing vessels based on sufficient preliminary evidence. In the explanation mentioned that special action is performed is not arbitrary but is done when the investigator and/or fisheries supervisor convinced that foreign fishing vessels that have committed the crime of fisheries. For the commander of KRI the act of shooting and/or sinking foreign fishing vessels must meet the requirements of the state where the vessels are doing things that are contrary to the pursuit, arrest, inspection and investigation, for example escape or resistance. Research results can be concluded that the act of shooting or sinking and exterminating evidence of foreign-flagged fishing vessels that sufficient evidence of a criminal act fisheries in WPP RI in practice can be done by means of hot pursuit, in the process of investigation and carry out the determination of the court. Due to the sinking of the vessel does not bring bad influence on Homeland relationships with the countries concerned and will provide a deterrent to potential offenders of other fisheries crime act. Government stern action against the perpetrators of the illegal fishing carried out in accordance with the procedures and provisions of applicable law.Keywords: Illegal Fishing, the Legality of the Navy (TNI AL) Investigators, Sinking Foreign Fishing Vessel